The ultimate Vue JS 2 developers course (Packt Publishing, 2017)
"This Course contains all Vue concepts from beginner to advanced, way to create a universal application with server-side rendering and uses popular plugins from the Vue ecosystem like vue-router and vue-resources."--Resource description page.